Determinants of intention to adopt social customer relationship management services and their effects on marketing performance among Malaysian start-up companies - Hasani, Tahereh (2016)
Social networking technologies and social media have changed almost all aspects of our lives and created a lot of business opportunities. The rise of social media affected Customer Relationship Management (CRM) by developing a new concept called “social CRM” (SCRM). SCRM merges traditional CRM and Web 2.0 tools with collaborative elements. SCRM changed one-way communications with customers into two-way, real-time interactions. This shift engages customers in collaborative conversations in order to provide mutually beneficial value in a trusted & transparent business environment. The fast rate of advancement in technologies gives space to the development of new breed of temporary companies striving towards developing a scalable, repeatable and profitable business models which are called start-up businesses. Naturally, these companies are having very limited advertising, marketing, and customer service capabilities. SCRM technologies may provide these companies with efficient and low-cost capabilities to manage their customers and reach to the new markets. In spite of the vital importance of adopting SCRM solutions in start-up companies very limited scholarly research was conducted to investigate factors affecting SCRM adoption in start-up companies and effects of SCRM adoption on marketing performance of start-up businesses. The purpose of this study is two-folded. First, detecting and investigating the relationships between factors affecting SCRM adoption among start-up companies and second investigating the mediating role of SCMR adoption on start-up companies marketing performance in Malaysia. This research primary data was collected from 389 start-up companies in Malaysia. The unit of analysis was individuals who are working in start-up companies. Collected data was first summarised using Exploratory Factor Analyses (EFA) and then evaluated in two stages. In the first stage, Confirmatory Factor Analysis (CFA) technique was utilised to confirm the measurement model. Afterward, hypothesised relationships were analysed through multivariate analysis process using Structural Equation Modelling (SEM) via Analysis of Moment Structures (AMOS) software. The findings of this research indicated direct positive effects of all hypothesised technological and environmental characteristics and availability of internal financial resources on both SCRM adoption and marketing performance of start-up companies. However, managerial characteristic and availability of business incubation solutions did not have any positive effect on SCRM adoption or marketing performance. Moreover, it was detected that SCRM adoption mediates the relationship between technological, environmental and organisational (only availability of internal financial resources) characteristic and marketing performance of start-up companies in Malaysia. This study showed that adopting SCRM technologies would promote marketing performance of start-up companies. Moreover, it was shown that among different SCRM solutions, start-up companies should choose the one with the highest perceived advantage as it would have the most significant positive effect on their marketing performance. Compatibility, observability, and trialability are the next important factors to choose between different SCRM solutions. In addition, it was detected that venture capitalists support has the most positive influence on marketing performance and SCRM adoption even more than governmental supports in the context of Malaysia.